Implementasi Aspek Kompetensi (Sikap) dan Habit (Kebiasaan) pada Pendidikan Karakter di SMP IT at-Taqwa - Salsabila, Syahnaz Apriliana Putri; Audina, Selly Eka; Wulandari, Riska Putri Ayu; Amanda, Mariska Dwi (Lembaga Yasin AlSys, 2023)
Educational institutions are an essential forum for producing young people who are better than the current generation through character education. A golden generation can be obtained by implementing character education through attitudes and habits. This research uses a qualitative description method to analyze how character education is instilled at SMP IT AT TAQWA. In this research, there were respondents from mrs. Menik as deputy head of public relations and student affairs with whom we received information for writing this article. To collect information, researchers conducted in-depth interviews and observations. The in-depth interview aims to find out opinions and how to instill character education in students. Observations were carried out to collect information about the cultivation of character education at SMP IT AT TAQWA. This educational institution implements character education through competencies (attitudes) and habits by carrying out various activities that are rarely available in other educational institutions. Competence (attitude) is applied through discipline, one of which is before entering class by using fingerprints. Then the habit is to perform the Dhuha prayer before learning begins. And through the implementation of paperless, without a bell and other independent activities. The implementation of character education at AT TAQWA IT Middle School should be appreciated, by upholding discipline, good habits leading to religion and also upholding honesty.